Traumatic Lower Limb Injury and Microsurgical Free Flap Reconstruction with the Use of Negative Pressure Wound Therapy: Is Timing Crucial? - Raju, Ashvin; Ooi, Adrian; Ong, Yee Siang; Tan, Bien Keem (Journal of Reconstructive Microsurgery, 2014)
Background The timing of microsurgical free flap reconstruction for traumatic lower limb injury has been described as being optimal if conducted within the early period following injury, as higher rates of infection and flap loss were reported in the subsequent time period. However, for various reasons, reconstruction of these defects may be delayed. The aim of this article is to show that adequate debridement, negative pressure wound dressing, and sound reconstructive principles has led to increased free flap success rates regardless of the period between injury and reconstruction.Patients and Methods A 10-year retrospective single-center analysis of 50 traumatic lower limb cases from 2002 to 2012 was conducted. All patients had microsurgical free flap reconstruction after a period of negative pressure wound therapy (NPWT). Patient factors and reconstructive methods were analyzed and outcomes were compared.Results Mean interval between admission and free flap coverage was 17.5 days, and patients underwent NPWT for an average of 12 days (range, 1–35). Approximately 8% of patients had postoperative infections. Overall free flap success rate was 96%. Approximately 90% of patients were able to return to their premorbid footwear, with 96% able to mobilize independently approaching the end of their follow-up period.Conclusion Our study shows that traumatic lower limb reconstruction in the delayed period is no longer associated with high rates of flap failure. Improvements in microsurgery and the advent of NPWT have made timing no longer crucial in free flap coverage of traumatic lower limb injuries.
Keywords: negative pressure wound therapy; lower limb trauma; free flap